On the Thermodynamic Preconditioning of Arctic Air Masses and the Role of Tropopause Polar Vortices for Cold Air Outbreaks From Fram Strait - Papritz, Lukas; id_orcid:0 000-0002-2047-9544; Rouges, Emmanuel; Aemisegger, Franziska; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Journal of Geophysical Research: Atmospheres, 2019)
ISSN:0148-0227 ISSN:2169-897X